Energy Efficiency and Renewable Energy Supply for the G-7 Countries, with Emphasis on Germany - Strand, Jon (IMF Working Papers; Working Paper ;, 2007)
This paper discusses structure, impact, costs, and efficiency of renewable energy supply in the eight largest advanced economies (the G-7 plus Spain), with focus on Germany. Renewables production costs are compared to benefits, defined as reductions in net carbon emissions; technological innovation, and increased energy security. The latter part of the paper centers on Germany, the main European producer of non-traditional renewables. We question whether the level of subsidies can be justified, relative to other means to increase energy security and reduce carbon emissions. We also find an excessive emphasis on current productive activity, relative to development of new technologies.